Hot-rolled steel sheet
Patent Information
- Application Number
- CN202180101291.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-09-06
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2041-09-06
AI Technical Summary
然而,如果将钢板高强度化,则一般而言韧性发生劣化
根据本发明的上述方案,能够提供具有高强度以及优异的疲劳强度、韧性及延展性的热轧钢板。根据该热轧钢板,能够谋求汽车等的车身的轻量化及耐久性提高,因此工业价值高。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to hot-rolled steel sheets. More specifically, it relates to hot-rolled steel sheets having high strength as well as excellent fatigue strength, toughness, and ductility. Background Technology
[0002] In recent years, research has been actively conducted on the application of high-strength steel sheets in automotive components with the aim of improving vehicle durability and crash safety. However, increasing the strength of steel sheets generally leads to a deterioration in toughness. Therefore, achieving high strength without compromising material properties is a crucial issue in the development of high-strength steel sheets. In particular, ensuring the fatigue durability of components using high-strength steel sheets in automotive components is of paramount importance. During component manufacturing, cracking can progress from the punching surface, and even using high-strength steel sheets may not necessarily improve the fatigue durability of the components.
[0003] In response, Patent Document 1 proposes a high-strength hot-rolled steel sheet with excellent bending workability. Its metal structure has a surface region with ferrite as the main phase and an internal region with bainite as the main phase. The proportion of the surface region in the thickness direction of the steel sheet is set to 1.0 to 5.0% of the total thickness of the surface and back sides of the steel sheet.
[0004] Patent document 2 proposes a high-strength hot-rolled steel sheet with excellent workability, which has a central part mainly composed of bainite and a surface part mainly composed of polygonal ferrite, the surface part being formed at least in the region from both surfaces of the steel sheet to a depth of 0.2 mm.
[0005] Patent document 3 proposes a high-strength steel sheet with excellent bending properties, which has low average Vickers hardness and standard deviation of hardness from the surface to half the thickness of the sheet.
[0006] Patent document 4 proposes a hot-rolled steel sheet that improves fatigue characteristics and surface machinability by controlling the martensite area fraction and Vickers hardness within a specified range in each depth direction of the sheet thickness.
[0007] Existing technical documents Patent documents Patent Document 1: International Publication No. 2014 / 171057 Patent Document 2: Japanese Patent Application Publication No. 2001-279378 Patent Document 3: International Publication No. 2018 / 151331 Patent Document 4: Japanese Patent Application Publication No. 2017-186634 Summary of the Invention
[0008] The problem that the invention aims to solve However, in the case of the hot-rolled steel sheets described in Patent Documents 1 to 3, the surface layer is mainly composed of ferrite, which softens the material, leaving room for further improvement in fatigue characteristics.
[0009] Furthermore, in the invention described in Patent Document 4, the surface layer is softened, leaving room for further improvement in fatigue strength. Moreover, since precipitation strengthening occurs within the plate thickness, dislocation movement in the ferrite is hindered, leaving room for further improvement in toughness from this perspective.
[0010] In recent years, driven by the need for further lightweighting of automobiles and the increasing complexity of component shapes, there has been a demand for high-strength hot-rolled steel sheets with higher fatigue strength and toughness.
[0011] The present invention was made in view of the aforementioned problems, the problem of which is to provide hot-rolled steel sheets having high strength as well as excellent fatigue strength and toughness. Furthermore, the object of the present invention is to provide hot-rolled steel sheets that, in addition to having the aforementioned properties, also possess excellent ductility, a property generally required for hot-rolled steel sheets used in automotive components.
[0012] Methods for solving problems Precipitation-strengthened microstructures exhibit excellent fatigue strength because they hinder dislocation movement. Therefore, these microstructures are frequently used in automotive running gear components. On the other hand, suppressing dislocation movement makes plastic deformation less likely, thus deteriorating impact characteristics (especially toughness). Therefore, it is presumed that fatigue strength and impact characteristics have an inverse relationship. To improve both fatigue strength and toughness, the inventors of this invention have conducted a detailed analysis of the deformation mechanisms of fatigue strength and impact strength. As a result, the inventors of this invention believe that the microstructure and hardness of the surface region of hot-rolled steel sheet have a significant impact on fatigue strength, while the microstructure and hardness of the internal region of hot-rolled steel sheet have a significant impact on crack propagation.
[0013] The main idea of the present invention, based on the above understanding, is as follows.
[0014] (1) The chemical composition of the hot-rolled steel plate of one embodiment of the present invention, expressed in mass percent, contains: C: 0.02~0.30% Si: 0.10~2.00% Mn: 0.5–3.0%, sol.Al: 0.10~1.00% Ti: 0.06~0.20%, P: Below 0.1000% S: Below 0.0100% N: below 0.0100% Nb: 0~0.100%, Ca: 0~0.0060%, Mo: 0–0.50%, Cr: 0~1.00%, V: 0~0.40%, Ni: 0~0.40%, Cu: 0–0.40% B: 0~0.0020%, and Sn: 0~0.20%, The remaining portion contains Fe and impurities. The internal metallic microstructure contains, by area percentage, 40–80% of one or two types of martensite and bainite, 20–60% of ferrite, and the remaining microstructure has an area percentage of less than 5%. The ratio of the ferrite area fraction αs in the surface region to the ferrite area fraction αc in the aforementioned internal region, i.e., αs / αc, is 1.15 to 2.50. The ratio of the Vickers hardness Hvs of the aforementioned surface region to the Vickers hardness Hvc of the aforementioned internal region, i.e., (1-Hvs / Hvc), is less than 0.20. The tensile strength of the hot-rolled steel plate is above 980 MPa.
[0015] (2) The hot-rolled steel plate according to (1) above, wherein the above chemical composition may also contain one or more elements selected from the following elements in mass percent: Nb: 0.010~0.100% Ca: 0.0005~0.0060% Mo: 0.02–0.50% Cr: 0.02~1.00% V: 0.01~0.40%, Ni: 0.01~0.40%, Cu: 0.01–0.40% B: 0.0001~0.0020%, and Sn: 0.01~0.20%.
[0016] Invention Effects According to the above-described solution of the present invention, a hot-rolled steel sheet with high strength, excellent fatigue strength, toughness, and ductility can be provided. Based on this hot-rolled steel sheet, it is possible to achieve lightweighting and improved durability of automobile bodies, thus possessing high industrial value. Detailed Implementation
[0017] A hot-rolled steel sheet according to one embodiment of the present invention (hereinafter, sometimes referred to as the hot-rolled steel sheet of this embodiment) will be described. However, the present invention is not limited to the configuration disclosed in this embodiment, and various modifications can be made without departing from the spirit of the present invention.
[0018] The essential constituent conditions of the present invention will be described in detail below. First, the reasons for limiting the chemical composition of the hot-rolled steel sheet in this embodiment will be explained.
[0019] The following limits the numerical ranges indicated by the brackets “~”, including both the lower and upper limits. Values expressed as “less than” or “more than” are not included in the range. In the following descriptions, “%” for chemical composition refers to “mass%” unless otherwise specified.
[0020] The hot-rolled steel sheet of this embodiment has the following chemical composition (by mass%): C: 0.02–0.30%, Si: 0.10–2.00%, Mn: 0.5–3.0%, sol.Al: 0.10–1.00%, Ti: 0.06–0.20%, P: ≤0.1000%, S: ≤0.0100%, N: ≤0.0100%, and the remainder: Fe and impurities. Each element is described in detail below.
[0021] <C:0.02~0.30%> Carbon (C) is an important element for improving the strength of hot-rolled steel sheets. To obtain the desired strength, the C content is set to 0.02% or more, preferably 0.04% or more.
[0022] On the other hand, if the carbon content exceeds 0.30%, the toughness of the hot-rolled steel sheet deteriorates. Therefore, the carbon content is set to 0.30% or less, preferably 0.20% or less.
[0023] <Si:0.10~2.00%> Si is an element that inhibits the formation of carbides during ferrite phase transformation and improves the toughness of hot-rolled steel sheets. To achieve this effect, the Si content is set to 0.10% or more. Preferably, it is 0.20% or more or 0.50% or more.
[0024] On the other hand, if the Si content exceeds 2.00%, the toughness of the hot-rolled steel sheet deteriorates. Therefore, the Si content is set to 2.00% or less, preferably 1.50% or less.
[0025] <Mn:0.5~3.0%> Mn is an element effective for increasing the strength of hot-rolled steel sheets by improving hardenability and providing solid solution strengthening. To obtain this effect, the Mn content is set to 0.5% or more, and preferably 1.0% or more.
[0026] On the other hand, if the Mn content exceeds 3.0%, MnS that is harmful to toughness and fatigue strength is formed. Therefore, the Mn content is set to 3.0% or less, and preferably 2.5% or less or 2.0% or less.
[0027] <sol.Al:0.10~1.00%> Al is an important element for controlling ferrite phase transformation. To obtain this effect, the sol.Al content is set to 0.10% or more, and preferably 0.15% or more or 0.20% or more.
[0028] On the other hand, if the sol.Al content exceeds 1.00%, alumina precipitated in clusters is formed, which degrades the toughness of the hot-rolled steel sheet. Therefore, the sol.Al content is set to 1.00% or less, and preferably 0.80% or less or 0.50% or less.
[0029] It should be noted that sol.Al refers to acid-soluble Al, which represents solid solution Al present in steel in a solid solution state.
[0030] <Ti:0.06~0.20%> Ti is an element that provides precipitation strengthening of ferrite, and is an important element for obtaining a desired amount of ferrite through controlling ferrite phase transformation. To obtain excellent fatigue strength through precipitation strengthening and control of ferrite phase transformation, the Ti content is set to 0.06% or more, and preferably 0.08% or more.
[0031] On the other hand, if the Ti content exceeds 0.20%, inclusions originating from TiN are formed, which degrades the toughness of the hot-rolled steel sheet. Therefore, the Ti content is set to 0.20% or less, and preferably 0.16% or less or 0.13% or less.
[0032] <P:0.1000%以下> P is an impurity, and a lower P content is more preferred. In particular, if the P content exceeds 0.1000%, the workability and weldability of the hot-rolled steel sheet are significantly reduced, and the fatigue strength is also reduced. Therefore, the P content is set to 0.1000% or less, and preferably 0.0500% or less or 0.0200% or less.
[0033] The lower limit of the P content does not need to be specifically specified, but from the viewpoint of refining cost, it is preferably set to 0.0010% or more.
[0034] <S:0.0100%以下> S is an impurity, and a lower S content is more preferable. Specifically, if the S content exceeds 0.0100%, a large amount of inclusions such as MnS that are detrimental to the isotropy of toughness will be formed. Therefore, the S content is set to 0.0100% or less. When more excellent toughness is required, the S content is preferably set to 0.0060% or less, and more preferably 0.0050% or less.
[0035] The lower limit of the S content is not particularly required to be specified, but from the viewpoint of refining cost, it is preferably set to 0.0001% or more.
[0036] <N: 0.0100% or less> N is an impurity. If the N content exceeds 0.0100%, coarse Ti nitrides are formed in the high-temperature region, thereby deteriorating the toughness of the hot-rolled steel sheet. Therefore, the N content is set to 0.0100% or less, and preferably 0.0060% or less or 0.0050% or less.
[0037] The lower limit of the N content is not particularly required to be specified, but from the viewpoint of refining cost, it is preferably set to 0.0001% or more.
[0038] The hot-rolled steel sheet of the present embodiment may contain the above chemical components, with the balance being Fe and impurities. In the present embodiment, the term "impurities" refers to components mixed in from raw materials such as ore and scrap, the manufacturing environment, and / or components allowed within a range that does not adversely affect the hot-rolled steel sheet of the present embodiment.
[0039] Although not required for achieving desired properties, the following optional elements may be contained to reduce manufacturing variation and further improve the strength of the hot-rolled steel sheet. However, since containing these elements is not mandatory, the lower limit of the content of these elements is 0%. It should be noted that if the content of each optional element is lower than the lower limit value described below, the element can be regarded as an impurity.
[0040] <Nb: 0.010 to 0.100%> Nb is an element that has the effect of increasing the strength of a hot-rolled steel sheet through grain size refinement of the hot-rolled steel sheet and precipitation strengthening of NbC. When it is desired to reliably obtain this effect, the Nb content is preferably set to 0.010% or more.
[0041] On the other hand, when the Nb content exceeds 0.100%, the above effect becomes saturated. Therefore, even when Nb is contained, the Nb content is set to 0.100% or less, and preferably 0.060% or less.
[0042] <Ca: 0.0005 to 0.0060%> Ca is an element that disperses fine oxides in large quantities during the deoxidation of molten steel, thereby refining the microstructure of hot-rolled steel sheets. Furthermore, Ca fixes sulfur in steel into spherical CaS, inhibits the formation of elongated inclusions such as MnS, and improves the porosity of hot-rolled steel sheets. To reliably achieve these effects, it is preferable to set the Ca content to 0.0005% or more.
[0043] On the other hand, the above-mentioned effect saturates even when the Ca content exceeds 0.0060%. Therefore, even when Ca is present, the Ca content is set to 0.0060% or less. Preferably, it is 0.0040% or less.
[0044] <Mo:0.02~0.50%> Mo is an effective element for strengthening the precipitation of ferrite. To reliably obtain this effect, it is preferable to set the Mo content to 0.02% or more. More preferably, it is 0.10% or more.
[0045] On the other hand, if the Mo content becomes excessive, the slab's slab's susceptibility to cracking increases, making slab processing difficult. Therefore, even when Mo is present, the Mo content is set to 0.50% or less. Preferably, it is 0.30% or less.
[0046] <Cr:0.02~1.00%> Cr is an effective element for improving the strength of hot-rolled steel sheets. To reliably achieve this effect, it is preferable to set the Cr content to 0.02% or more. More preferably, it is 0.10% or more.
[0047] On the other hand, if the Cr content becomes excessive, the ductility of the hot-rolled steel sheet decreases. Therefore, even when Cr is present, the Cr content is set to 1.00% or less. Preferably, it is 0.80% or less.
[0048] <V:0.01~0.40%> V enhances the strength of hot-rolled steel sheets through strengthening by precipitates, grain refinement by inhibiting ferrite grain growth, and dislocation strengthening by inhibiting recrystallization. To reliably achieve these effects, it is preferable to set the V content to 0.01% or more.
[0049] On the other hand, if the V content is excessive, a large amount of carbonitrides will precipitate, thereby reducing the formability of the hot-rolled steel sheet. Therefore, the V content is set to 0.40% or less, preferably 0.20% or less.
[0050] <Ni:0.01~0.40%> Ni suppresses phase transformation at high temperatures and improves the strength of hot-rolled steel sheets. To reliably achieve this effect, it is preferable to set the Ni content to 0.01% or higher.
[0051] On the other hand, if the Ni content is excessive, the weldability of the hot-rolled steel sheet decreases. Therefore, the Ni content is set to 0.40% or less, preferably 0.20% or less.
[0052] <Cu:0.01~0.40%> Cu exists in steel in the form of fine particles, which increases the strength of hot-rolled steel sheets. To reliably achieve this effect, it is preferable to set the Cu content to 0.01% or more.
[0053] On the other hand, if the Cu content is excessive, the weldability of the hot-rolled steel sheet decreases. Therefore, the Cu content is set to 0.40% or less, preferably 0.20% or less.
[0054] <B:0.0001~0.0020%> Boron (B) inhibits phase transformation at high temperatures and improves the strength of hot-rolled steel sheets. To reliably achieve this effect, it is preferable to set the B content to 0.0001% or higher.
[0055] On the other hand, if the boron content is excessive, boron precipitates will form, thereby reducing the strength of the hot-rolled steel sheet. Therefore, the boron content is set to 0.0020% or less, preferably 0.0005% or less.
[0056] <Sn:0.01~0.20%> Sn is an element that inhibits grain coarsening and improves the strength of hot-rolled steel sheets. To reliably achieve this effect, it is preferable to set the Sn content to 0.01% or more.
[0057] On the other hand, if the Sn content becomes excessive, the steel becomes embrittled and prone to fracture during rolling. Therefore, the Sn content is set to 0.20% or less, preferably 0.10% or less.
[0058] The chemical composition of the hot-rolled steel sheet described above can be determined using general analytical methods. For example, it can be determined using ICP-AES (Inductively Coupled Plasma-Atomic Emission Spectrometry). It should be noted that sol.Al can be determined by ICP-AES using the filtrate obtained after heating and decomposing the sample with acid. C and S can be determined using the combustion-infrared absorption method, and N can be determined using the inert gas melting-thermal conductivity method.
[0059] Next, the metal structure of the hot-rolled steel sheet of this embodiment will be described.
[0060] The internal metal structure of the hot-rolled steel sheet of this embodiment contains, in terms of area ratio, 40-80% of one or two types of martensite and bainite, 20-60% of ferrite, and the area ratio of the remaining structure is less than 5%. The ratio of the ferrite area ratio αs of the surface region to the ferrite area ratio αc of the internal region, i.e., αs / αc, is 1.15-2.50. The ratio of the Vickers hardness Hvs of the surface region to the Vickers hardness Hvc of the internal region, i.e., (1-Hvs / Hvc), is 0.20 or less.
[0061] It should be noted that the so-called internal region refers to the area of the hot-rolled steel sheet centered at a depth of 1 / 4 of the sheet thickness from the surface, extending to a depth of 1 / 8 of the sheet thickness from the surface. Furthermore, the so-called surface region refers to the area from the surface of the hot-rolled steel sheet to a depth of 20 μm from the surface.
[0062] Regarding the microstructure dominated by martensite and bainite, the microstructure is fine and exhibits excellent toughness. However, many aspects of its mechanism are unclear, but it is known that steel with a microstructure dominated by martensite and bainite has inferior fatigue strength compared to precipitation-strengthened steel and ferrite-martensite composite (DP) steel. On the other hand, for precipitation-strengthened steel and DP steel, fatigue strength and toughness are inferior because the high-speed dislocation movement in ferrite is hindered. Previously, for automotive parts, steel sheet microstructures were manufactured according to the required properties, but with further development towards higher strength, achieving both high fatigue strength and high toughness has become difficult. Therefore, the hot-rolled steel sheet of this embodiment differs from conventional technology by increasing the ferrite content in the surface region, thereby flexibly utilizing the excellent fatigue strength of the ferrite-martensite composite microstructure and precipitation strengthening, while flexibly utilizing a metallic microstructure dominated by one or both of martensite and bainite, which exhibit excellent toughness, in the internal region. As a result, a high strength of over 980 MPa, as well as excellent fatigue strength, toughness, and ductility can be obtained.
[0063] Metal structure of internal region The microstructure of the internal region of hot-rolled steel sheet significantly affects its toughness. Therefore, the microstructure of the internal region is predominantly low-temperature transformation microstructure. Low-temperature transformation microstructure refers to martensite and bainite. When the combined area ratio of these microstructures is less than 40%, the toughness of the hot-rolled steel sheet deteriorates. Therefore, the combined area ratio of martensite and bainite is set to 40% or more. Preferably, it is 45% or more, and more preferably 50% or more.
[0064] On the other hand, if the combined area ratio of martensite and bainite exceeds 80%, the fatigue strength of the hot-rolled steel sheet deteriorates due to the increased hardness difference between the martensite and bainite structures in the surface region. Therefore, the combined area ratio of martensite and bainite is set to 80% or less. Preferably, it is 75% or less, and more preferably 70% or less.
[0065] In this embodiment, if the metal structure of the internal region contains only one of martensite or bainite, it is acceptable as long as the content of only one of martensite or bainite is within the above-mentioned range. If it contains both martensite and bainite, it is acceptable as long as the total content of martensite and bainite is within the above-mentioned range.
[0066] If the ferrite area fraction in the internal metal structure is less than 20%, the fatigue strength of the hot-rolled steel sheet will be poor due to the increased hardness difference between the internal and external metal structures. Therefore, the ferrite area fraction is set to 20% or more. Preferably, it is 25% or more, and more preferably 30% or more.
[0067] On the other hand, if the ferrite area ratio exceeds 60%, strain cannot be mitigated due to the precipitation of ferrite grains, and processability cannot be guaranteed, resulting in a deterioration in the toughness of the hot-rolled steel sheet. Therefore, the ferrite area ratio is set to 60% or less. Preferably, it is 55% or less, and more preferably 50% or less.
[0068] The residual microstructure in the internal region is less than 5% by area. The residual microstructure is one or more of pearlite and retained austenite. The residual microstructure is preferably less than 3%, more preferably less than 2.5%, and even more preferably less than 2%.
[0069] Metall structure in the surface area In the microstructure of the surface region of hot-rolled steel sheet, when the ratio of the ferrite area fraction αs in the surface region to the ferrite area fraction αc in the interior region, i.e., αs / αc, is less than 1.15, the suppression of dislocation movement in the ferrite becomes insufficient, and the fatigue strength of the hot-rolled steel sheet deteriorates. Therefore, αs / αc is set to 1.15 or more. Preferably, it is 1.20 or more, or 1.30 or more, and more preferably 1.50 or more.
[0070] On the other hand, if αs / αc exceeds 2.50, the hardness difference between the carbon concentrated in the interior of the plate during the ferrite phase transformation and the internal metal structure becomes larger, resulting in poor toughness and / or fatigue strength of the hot-rolled steel plate. Therefore, αs / αc is set to 2.50 or less. Preferably, it is 2.20 or less, and more preferably 2.00 or less.
[0071] In the microstructure of the surface region of hot-rolled steel sheet, the ratio of the total area fraction βs of martensite and bainite in the surface region to the total area fraction βc of martensite and bainite in the interior region, i.e., βs / βc, is preferably 0.30 to 0.90. By having βs / βc below 0.90, dislocation movement in martensite and bainite can be sufficiently suppressed, thereby improving the fatigue strength of the hot-rolled steel sheet. βs / βc is more preferably below 0.85, and even more preferably below 0.80.
[0072] On the other hand, by having a βs / βc ratio of 0.30 or higher, the concentration of carbon in the interior of the plate thickness during the phase transformation of martensite and bainite can be suppressed, thus preventing a large hardness difference between the carbon and the internal metal structure and the interior region, thereby improving the toughness and fatigue strength of the hot-rolled steel plate. A βs / βc ratio of 0.40 or higher is more preferred, even more preferred is 0.45 or higher, and even more preferred is 0.50 or higher.
[0073] The microstructure of the surface region may also contain 30-80% ferrite by area ratio. In addition, the microstructure of the surface region may also contain 20-70% of one or more of bainite, martensite, pearlite and retained austenite as the remaining microstructure other than ferrite by area ratio.
[0074] Methods for determining metal structure A sample is cut from a hot-rolled steel sheet with a thickness section perpendicular to the surface for observation. The sample's thickness section is ground using #600 to #1500 silicon carbide paper, then refined to a mirror finish using a liquid obtained by dispersing diamond powder with a particle size of 1 to 6 μm in a diluent such as alcohol or pure water, followed by nitric acid ethanol etching. Next, multiple fields of view are photographed at arbitrary locations along the length of the sample section using a thermal field emission scanning electron microscope (JEOL JSM-7001F). Equally spaced grids are drawn on the photographs, and the microstructure at each grid point is identified. The number of grid points corresponding to each microstructure is calculated, and the area ratio of each microstructure is obtained by dividing by the total number of grid points. The more grid points, the more accurately the area ratio can be calculated. In this embodiment, the grid spacing is set to 2 μm × 2 μm, and the total number of grid points is set to 1500.
[0075] Regions where cementite precipitates in lamellar form within the grains are identified as pearlite. Regions with low brightness and where no underlying microstructure is observed are identified as ferrite. Regions with high brightness and where the underlying microstructure is not revealed by etching are identified as martensite and retained austenite. Regions that do not meet any of the above criteria are identified as bainite. The martensite area ratio is obtained by subtracting the retained austenite area ratio obtained through EBSD analysis (described later) from the martensite and retained austenite area ratios obtained from photographs.
[0076] The sample was cut from the same location as described above, with a cross-section perpendicular to the surface that is observable. The cross-section was then polished using #600 to #1500 silicon carbide paper, followed by a mirror finish using a liquid obtained by dispersing diamond powder with a particle size of 1–6 μm in an alcohol-based diluent or pure water. Next, the sample was polished for 8 minutes at room temperature using colloidal silica without an alkaline solution to remove strain introduced into the sample surface. Crystal orientation information was obtained by electron backscatter diffraction at arbitrary locations along the length of the sample cross-section at measurement intervals of 0.1 μm. For the measurements, an EBSD apparatus consisting of a thermal field emission scanning electron microscope (JEOL JSM-7001F) and an EBSD detector (TSL DVC5 detector) was used. The vacuum level within the EBSD apparatus was set to 9.6 × 10⁻⁶. -5 Below Pa, the accelerating voltage was set to 15 kV, the irradiation current level to 13, and the electron beam irradiation level to 62. The obtained crystal orientation information was analyzed using the "Phase Map" function within the "OIM Analysis" software (registered trademark) included in the EBSD analysis device to calculate the area ratio of retained austenite. It should be noted that crystals with an fcc crystal structure were identified as retained austenite.
[0077] By performing the aforementioned measurements on regions ranging from 1 / 8 to 3 / 8 of the plate thickness from the surface and on the surface of the hot-rolled steel plate at a depth of 20 μm from the aforementioned surface, the area ratio of the metal structure in the internal and surface regions was obtained.
[0078] The ratio of the Vickers hardness difference between the surface region and the interior region is below 0.20. If the ratio of the Vickers hardness Hvs in the surface region to the Vickers hardness Hvc in the interior region, i.e., (1-Hvs / Hvc), exceeds 0.20, the surface region softens, and the fatigue strength of the hot-rolled steel sheet deteriorates. Therefore, the ratio of the hardness difference between Hvs and Hvc, i.e., (1-Hvs / Hvc), is set to 0.20 or less. Preferably, it is 0.15 or less, and more preferably 0.10 or less.
[0079] The smaller the ratio of the hardness difference between Hvs and Hvc (1-Hvs / Hvc), the better. However, from a manufacturing point of view, it can also be set to -0.10 or higher, 0.00 or higher, or 0.01 or higher.
[0080] Vickers hardness test method Test pieces are cut from hot-rolled steel sheets at a thickness perpendicular to the surface for observation. The thickness section of the test piece is ground using #600 to #1500 silicon carbide paper, and then polished to a mirror finish using a liquid obtained by dispersing diamond powder with a particle size of 1–6 μm in a diluted solution such as alcohol or pure water. This thickness section is used as the testing surface. Using a micro Vickers hardness tester, Vickers hardness is measured at intervals of at least three times the indentation length, with a load of 1 kgf, in a region of 1 / 8 to 3 / 8 of the thickness from the surface of the testing surface. A total of 20 points are measured, and the average value is calculated to obtain the Vickers hardness Hvc of the internal metal structure. Similarly, Vickers hardness is measured in a region from the surface to a depth of 20 μm from the surface of the testing surface, and the average value of 20 points is calculated to obtain the Vickers hardness Hvs of the surface metal structure. Using the obtained Hvs and Hvc, the Vickers hardness difference ratio is obtained by calculating (1-Hvs / Hvc).
[0081] The tensile (maximum) strength of the hot-rolled steel sheet in this embodiment is 980 MPa or higher. Preferably, it is 1000 MPa or higher. If the tensile strength is lower than 980 MPa, the application of the parts is limited, and the contribution to vehicle body lightweighting is small. There is no need to specifically limit the upper limit, but from the viewpoint of suppressing die wear, it can also be set to 1500 MPa or lower or 1300 MPa or lower.
[0082] Furthermore, the total elongation of the hot-rolled steel sheet in this embodiment can be 10% or more, and the absorbed energy at -20°C can be 80 J / cm. 2 In addition, the fatigue limit ratio (fatigue strength / tensile strength) can also be above 0.48.
[0083] Tensile strength and total elongation were evaluated by tensile testing according to JIS Z 2241:2011. The test piece was set as test piece No. 5 of JIS Z 2241:2011. The tensile test piece was collected at a distance of 1 / 4 from the end in the width direction of the plate, and the direction perpendicular to the rolling direction was taken as the length direction.
[0084] Regarding toughness, firstly, a small V-notch test piece of 2.5 mm, as specified in JIS Z 2242:2018, is collected from a location close to the collection point of the test piece used in the tensile test. The absorbed energy is determined by performing a Charpy impact test with a C-direction notch at -20°C using this test piece. For hot-rolled steel sheets with a thickness less than 2.5 mm, the entire thickness is tested.
[0085] Fatigue strength was determined according to JIS Z 2275:1978 using a Schenker plane bending fatigue testing machine. The stress load during testing was varied, and the test speed was set to 30 Hz. The test was conducted over 10 minutes. 7 Fatigue strength during 10 cycles. Then, by 10 7 The fatigue limit ratio (fatigue strength / tensile strength) is calculated by dividing the fatigue strength at each cycle by the tensile strength determined by the above tensile test.
[0086] The thickness of the hot-rolled steel sheet in this embodiment is not particularly limited, but can be set to 1.2 to 8.0 mm. When the thickness of the hot-rolled steel sheet is less than 1.2 mm, it becomes difficult to ensure the rolling completion temperature, and the rolling load becomes too large, which may make hot rolling difficult. Therefore, the thickness of the hot-rolled steel sheet in this embodiment can also be set to 1.2 mm or more. Preferably, it is 1.4 mm or more. On the other hand, when the thickness exceeds 8.0 mm, it may become difficult to obtain the above-mentioned metal structure after hot rolling. Therefore, the thickness can also be set to 8.0 mm or less. Preferably, it is 6.0 mm or less.
[0087] The hot-rolled steel sheet of this embodiment, having the aforementioned chemical composition and metallic structure, can also be surface-treated to produce a steel sheet by applying a coating to its surface for purposes such as improving corrosion resistance. The coating can be an electroplated coating or a hot-dip galvanized coating. Examples of electroplated coatings include electroplated zinc layers and electroplated Zn-Ni alloy layers. Examples of hot-dip galvanized coatings include hot-dip galvanized layers, alloyed hot-dip galvanized layers, hot-dip aluminized layers, hot-dip Zn-Al alloy layers, hot-dip Zn-Al-Mg alloy layers, and hot-dip Zn-Al-Mg-Si alloy layers. The coating amount is not particularly limited and can be set as before. Furthermore, appropriate chemical conversion treatment (e.g., coating and drying with a silicate-based chromium-free chemical conversion solution) can be performed after plating to further improve corrosion resistance.
[0088] Regardless of the manufacturing method, the hot-rolled steel sheet of this embodiment achieves its desired effect by having the aforementioned chemical composition and metallic structure. However, the hot-rolled steel sheet of this embodiment can be stably obtained using the manufacturing method shown below, and is therefore preferred.
[0089] In the preferred manufacturing method of the hot-rolled steel sheet of this embodiment, bending is performed during the finishing rolling process of hot rolling to impart strain to the surface region, thereby promoting the ferrite phase transformation in the surface region. By rapidly cooling the surface region after the precipitation-strengthened ferrite has crystallized, not only ferrite but also martensite and bainite are generated in the internal region. Therefore, the hardness difference between the precipitation-strengthened surface region and the internal region, which has a low-temperature phase transformation structure without precipitation strengthening, can be reduced.
[0090] Hot rolling The heating temperature of the slab has a significant impact on the elimination of solution formation and elemental segregation. By setting the heating temperature of the slab to 1100°C or higher, it is possible to prevent insufficient elimination of solution formation and elemental segregation, thereby suppressing the deterioration of the tensile properties and toughness of the product. Furthermore, by setting the heating temperature of the slab to 1350°C or lower, the effect of eliminating solution formation and elemental segregation can be saturated. Therefore, the heating temperature of the slab is preferably set to 1100–1350°C, and more preferably 1150–1300°C.
[0091] It should be noted that the temperatures of the slab and the steel plate in this embodiment refer to the surface temperatures of the slab and the steel plate, respectively.
[0092] In finishing rolling, the slab is rolled multiple times continuously through a finishing mill stand. In finishing rolling, it is preferable to set the temperature of the hot-rolled steel sheet after the final pass (finished product temperature) to Ar3 or higher, and to set the reduction rate of the final pass to 12-45%.
[0093] It should be noted that the temperature of the hot-rolled steel sheet after the final pass is the lowest temperature in the finishing mill, which is rolled through multiple stands. When the entry plate thickness before the final pass is set to t0 and the exit plate thickness after the final pass is set to t1, the reduction rate after the final pass can be expressed as {(t0-t1) / t0}×100 (%). In addition, the Ar3 point is expressed by the following formula (1).
[0094] Ar3 point = 901 - 325 × C + 33 × Si - 92 × Mn + 287 × P + 40 × sol.Al Equation (1) The symbols for each element in equation (1) above represent the content (mass%) of each element. If the element is not present, substitute 0.
[0095] By setting the temperature of the hot-rolled steel sheet after the final pass of finishing rolling (finished product temperature) to above Ar3, the formation of ferrite in finishing rolling can be suppressed, resulting in the acquisition of the desired metal structure and properties.
[0096] By setting the reduction rate of the final pass in finishing rolling to 12% or more, recrystallization can be promoted during finishing rolling, and the microstructure of the metal in both the internal and surface regions can be preferably controlled, resulting in excellent fatigue strength. Furthermore, by setting the reduction rate of the final pass to 45% or less, the load increase on the rolling mill stand and the deterioration of the shape of the hot-rolled steel sheet after finishing rolling can be suppressed. Therefore, the reduction rate of the final pass in finishing rolling is preferably set to 12% to 45%, more preferably 15% to 45%.
[0097] Preferably, by performing a bending process between the final pass of the finishing rolling and the preceding pass, a strain of 0.002 to 0.020 is imparted to the surface region (the region from the surface to a depth of 20 μm) of the hot-rolled steel sheet. By setting the strain during bending to 0.002 or more, the desired metallic structure can be produced in the surface region. Therefore, the strain during bending is preferably set to 0.002 or more. More preferably, it is 0.003 or more or 0.004 or more.
[0098] Furthermore, by setting the strain during bending to 0.020 or less, it is possible to suppress the tendency to buckle and lose manufacturing stability during finish rolling. Moreover, by setting the strain during bending to 0.020 or less, it is possible to preferably control the microstructure of the metal in both the surface and internal regions. Therefore, the strain during bending is preferably set to 0.020 or less. More preferably, it is 0.015 or less or 0.010 or less.
[0099] It should be noted that bending is performed by pressing the steel plate from below between the frames using rollers. The strain during bending can be controlled by adjusting the bending angle by the amount of pressing or the diameter of the rollers.
[0100] For example, in the case of bending by pressing the steel plate from below between the frames, the strain during bending can be obtained by the following equation (2).
[0101] Strain = 1.5 × (plate thickness) × (amount pressed on) / (diameter of the front end of the pressing device) 2 Equation (2) The elapsed time from the completion of finishing rolling to the start of cooling is preferably set to 1.6 seconds or less. By setting the elapsed time from the completion of finishing rolling to the start of cooling to 1.6 seconds or less, strain recovery during bending and rolling can be suppressed, and the metal microstructure in the surface region can be preferably controlled.
[0102] Preferably, after finishing rolling, the material is cooled to a temperature range of 600–750°C at an average cooling rate of 40°C / second or higher as a primary cooling step, followed by air cooling for 2–6 seconds. It should be noted that, generally, the cooling rate during air cooling is 2–10°C / second.
[0103] By setting the stopping temperature of cooling at an average cooling rate of 40°C / second or higher to a temperature range of 600–750°C, followed by air cooling, the ferrite phase transformation can be promoted, and the desired amount of ferrite can be obtained.
[0104] Preferably, after air cooling, a secondary cooling process is performed, cooling at an average cooling rate of 60°C / second or higher to a temperature range below 200°C, followed by winding into a roll. By setting the average cooling rate up to the temperature range below 200°C to 60°C or higher, martensitic phase transformation can be promoted, and the desired amounts of martensite and bainite can be obtained.
[0105] Here, the average cooling rate is set as the value obtained by dividing the temperature drop of the steel plate from the start of cooling to the end of cooling by the required time from the start of cooling to the end of cooling.
[0106] Furthermore, there are cooling devices that have no air cooling zone in the middle and devices that have one or more air cooling zones in the middle. In this embodiment, any cooling device can be used. When using a cooling device with an air cooling zone, it is sufficient that the average cooling rate from the start to the end of cooling is within the range described above.
[0107] Since the hot-rolled steel sheet is coiled immediately after the secondary cooling, the coiling temperature is approximately equal to the cooling stop temperature of the secondary cooling. By setting the coiling temperature below 200°C, the formation of a large amount of polygonal ferrite or bainite can be suppressed, resulting in the desired metal microstructure and properties.
[0108] In addition, after coiling, the hot-rolled steel sheet can be subjected to temper rolling using conventional methods. Furthermore, pickling can be performed to remove the oxide scale formed on the surface. Alternatively, the aforementioned hot-dip galvanized or electro-galvanized coatings can be formed, or further chemical conversion treatment can be carried out.
[0109] According to the manufacturing method described above, hot-rolled steel sheets having the aforementioned metallic structure can be manufactured stably. Therefore, hot-rolled steel sheets with high strength, excellent fatigue strength, and toughness can be manufactured stably.
[0110] Example Next, the effects of one aspect of the present invention will be described in more detail through embodiments. However, the conditions in the embodiments are examples adopted to confirm the feasibility and effects of the present invention, and the present invention is not limited to these one example. Various conditions can be adopted by the present invention as long as they do not depart from the spirit of the present invention and achieve the purpose of the present invention.
[0111] Steel with the chemical composition shown in Table 1 was melted and slabs with a thickness of 240–300 mm were manufactured by continuous casting. Using the obtained slabs, hot-rolled steel sheets as shown in Tables 4 and 5 were obtained under the manufacturing conditions shown in Tables 2 and 3.
[0112] It should be noted that the bending process is performed by pressing the steel plate from below between the frames using rollers. The strain during bending is controlled by adjusting the bending angle based on the amount of pressing and the diameter of the rollers. In this case, the strain during bending is calculated using the above formula (2).
[0113] For the obtained hot-rolled steel sheet, the area fraction of the metal structure in the internal and surface regions, as well as the Vickers hardness, tensile strength, total elongation, absorbed energy at -20℃, and fatigue limit ratio, were determined using the methods described above. The obtained measurement results are shown in Tables 4 and 5.
[0114] Evaluation methods for the properties of hot-rolled steel sheets When the tensile strength (TS) is 980 MPa or higher, the hot-rolled steel sheet is deemed acceptable as having excellent strength. On the other hand, when the tensile strength (TS) is lower than 980 MPa, the hot-rolled steel sheet is deemed unacceptable as not having excellent strength.
[0115] If the total elongation is 10% or more, the hot-rolled steel sheet is deemed acceptable as having excellent ductility. On the other hand, if the total elongation is less than 10%, the hot-rolled steel sheet is deemed unacceptable as not having excellent ductility.
[0116] The absorption energy at -20℃ is 80 J / cm. 2 Under the above conditions, it is judged to be qualified as a hot-rolled steel sheet with excellent toughness. On the other hand, the absorbed energy at -20℃ is less than 80J / cm. 2 In such cases, the hot-rolled steel sheet, which is not of excellent toughness, is deemed unqualified.
[0117] When the fatigue limit ratio is 0.48 or higher, the hot-rolled steel sheet is deemed acceptable as having excellent fatigue strength. On the other hand, when the fatigue limit ratio is lower than 0.48, the hot-rolled steel sheet is deemed unacceptable as not having excellent fatigue strength.
[0118] [Table 1] [Table 2] [Table 3] [Table 4] [Table 5] If we observe Tables 4 and 5, we can see that the hot-rolled steel sheet of the present invention has high strength as well as excellent toughness, fatigue strength and ductility.
[0119] On the other hand, it can be seen that the hot-rolled steel sheet of the comparative example is inferior in one or more of the following: strength, toughness, and fatigue strength.
[0120] Industrial availability According to the above-described solution of the present invention, a hot-rolled steel sheet with high strength, excellent fatigue strength, toughness, and ductility can be provided. Based on this hot-rolled steel sheet, it is possible to achieve lightweighting of automobile bodies, integral molding of components, and shortening of processing steps, thereby improving fuel efficiency and reducing manufacturing costs, thus possessing high industrial value.
Claims
1. A hot-rolled steel plate, characterized in that, The chemical composition, expressed as a percentage by mass, is as follows: C:0.02~0.30%、 Si: 0.10~2.00% Mn: 0.5–3.0%, sol.Al: 0.10~1.00% Ti: 0.06~0.20%, P: Below 0.1000% S: Below 0.0100% N: below 0.0100% Nb: 0~0.100%, Ca: 0~0.0060%, Mo: 0–0.50%, Cr:0~1.00%、 V:0~0.40%、 Ni: 0~0.40%, Cu: 0–0.40% B: 0~0.0020%, and Sn: 0~0.20%, The remainder consists of Fe and impurities. The internal metallic microstructure contains, by area percentage, 40–80% of one or two types of martensite and bainite, 20–60% of ferrite, and the remaining microstructure has an area percentage of less than 5%. The ratio of the ferrite area fraction αs in the surface region to the ferrite area fraction αc in the internal region, i.e., αs / αc, is 1.15 to 2.
50. The ratio of the Vickers hardness Hvs of the surface region to the Vickers hardness Hvc of the inner region, i.e., (1-Hvs / Hvc), is less than 0.
20. The hot-rolled steel plate has a tensile strength of 980 MPa or higher. The inner region refers to the area of the hot-rolled steel plate, centered at a depth of 1 / 4 of the plate thickness from the surface, extending to a depth of 3 / 8 of the plate thickness from the surface. The surface region refers to the area on the surface of the hot-rolled steel plate up to a depth of 20 μm from the surface.
2. The hot-rolled steel plate according to claim 1, characterized in that, The chemical composition, expressed as a percentage by mass, contains one or more elements selected from the following: Nb: 0.010~0.100% Ca: 0.0005~0.0060% Mo: 0.02–0.50% Cr:0.02~1.00%、 V:0.01~0.40%、 Ni: 0.01~0.40%, Cu: 0.01–0.40% B: 0.0001~0.0020%, and Sn: 0.01~0.20%.
Citation Information
Patent Citations
Spark gap device and element thereof
CA500060A
High strength hot rolled steel sheet excellent in workability
JP2001279378A
Hot rolled steel sheet and manufacturing method therefor
JP2017186634A
High strength hot rolled steel sheet and method for producing same
WO2014171057A1
High strength steel plate
WO2018151331A1